Increasing the Operating Lifetime of Wearable Working Bodies of Agricultural Machines - Ya. P. Lobachevskiy; D. A. Mironov; A. V. Mironova (Сельскохозяйственные машины и технологии)
The eﬃciency of agricultural machine and tool operation is noted to significantly depend on the characteristics of the working bodies. The paper emphasizes the importance of working bodies’ reliability and operating lifetime which largely depend on wear resistance, strength, as well as design features. (Research purpose) To substantiate the choice of eﬀective modern directions to increase the operating lifetime of wearable agricultural machine working bodies, the choice of types and characteristics of the materials used and technological methods for their hardening. (Materials and methods) The many years’ experience of the FNAC VIM in this area has been studied. A concept analysis of the relevant technical information has been conducted. (Results and discussion) The basics and conditions of abrasive wear of agricultural machinery parts are presented. The concept of "structural wear resistance" is clarified. The paper analyzes the materials (steels, hard alloys) of the working bodies of the agricultural machines used in Russia and abroad. Their main comparative physical and mechanical characteristics are pointed out. A method is proposed for selecting basic design parameters based on the strength characteristics of the materials used. Surfacing technologies for hardening the agricultural machine working bodies are compared. The paper substantiates the most eﬀective technological options, individual technical and economic parameters, recommendations for the use of materials. (Conclusions) It is proved that the use of surfacing technologies leads to a 1.5-4.5-times increase in the operating lifetime of working bodies and significant economic eﬃciency.